2016
DOI: 10.1002/ange.201609601
|View full text |Cite
|
Sign up to set email alerts
|

Dibora[2]ferrocenophan: ein carbenstabilisiertes Diboren in einer gespannten cis‐Konfiguration

Abstract: Ungesättigte Brücken, die in gespannten ansa-Metallocenen zwei Cyclopentadienyl-Einheiten miteinander verbinden, sind äußerst selten und auf Kohlenstoff-Kohlenstoff-Doppelbindungen beschränkt. Die Synthese und Isolierung eines gespannten Ferrocenophans mit einer ungesättigten Brückea us zwei Boratomen, die isoelektronischm it einer C=C-Doppelbindung ist, wurde durch Reduktion eines carbenstabilisierten 1,1'-Bis(dihalogenboryl)ferrocens erstmals verwirklicht. Spektroskopische und elektrochemischeM essmethoden s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The boron atom lies in the plane of the imidazolin ring for 2 and the B−Se bond is not orthogonal to the plane [torsion angle (°) N1−C2−B1−Se1: 62.6(3), N2−C2−B1−Se1: 117.6(2)]. The B−Se bond length is 2.065(3) Å, which is in good agreement with the B−Se bond lengths (1.960–2.13 Å) reported for a small number of structurally characterized compounds featuring a B−Se bond [14a,19] . The B−C bond distance in 2 [1.615(4) Å] is marginally longer than that in 1 [1.602(3) Å] due to enhanced steric crowding around the central boron atom.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The boron atom lies in the plane of the imidazolin ring for 2 and the B−Se bond is not orthogonal to the plane [torsion angle (°) N1−C2−B1−Se1: 62.6(3), N2−C2−B1−Se1: 117.6(2)]. The B−Se bond length is 2.065(3) Å, which is in good agreement with the B−Se bond lengths (1.960–2.13 Å) reported for a small number of structurally characterized compounds featuring a B−Se bond [14a,19] . The B−C bond distance in 2 [1.615(4) Å] is marginally longer than that in 1 [1.602(3) Å] due to enhanced steric crowding around the central boron atom.…”
Section: Resultssupporting
confidence: 79%
“…However, there are examples of carbene supported boryl selenium compounds, but they were not prepared from carbene ⋅ BH 3 . For example, Braunschweig and coworkers studied the reactivity of an NHC stabilized dibora[2]ferrocenophane with excess diphenyldiselenide resulting in the cleavage of the B=B double bond and installation of two −SePh moieties on each boron atom [14a] . The same group later demonstrated the reduction of diphenyldiselenide by PMe 3 stabilized borylene leading to the formation of a cyclic alkyl amino carbene (cAAC) stabilized selenoborane radical [14b] .…”
Section: Introductionmentioning
confidence: 99%
“…16 In the case of group 13, in 1996 Wagner and co-workers investigated the geometry and electronic structure of borylferrocenes, FcBR 2 , revealing that there is an interaction between lled d-type orbitals at iron and the empty p orbital of boron, which causes bending of the BR 2 substituent toward the central iron atom. 17 In 2017, our group reported an NHC-stabilised dibora [2]ferrocenophane (VII, in Scheme 1) 18 that showed a strained cis conguration. Electrochemical measurements revealed that dibora [2]ferrocenophane has a remarkably low oxidation potential of E pa ¼ À1.56 V vs. the ferrocene/ferrocenium couple, corresponding to the oneelectron oxidation of the diborene unit, suggesting that the iron centre has an effect on the electrochemical properties of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical measurements revealed that dibora [2]ferrocenophane has a remarkably low oxidation potential of E pa ¼ À1.56 V vs. the ferrocene/ferrocenium couple, corresponding to the oneelectron oxidation of the diborene unit, suggesting that the iron centre has an effect on the electrochemical properties of the compound. 18 However, there remains no report on lowvalent aluminium compounds bearing redox-active ferrocenyl units.…”
Section: Introductionmentioning
confidence: 99%